On the career of a microeconomist - BAUMOL, W.J. (PSL Quarterly Review, 2013)
The paper is a contribution to a series of recollections and reflections on the professional experiences of distinguished economists which the Banca Nazionale del Lavoro Quarterly Review started in 1979. In it William J. Baumol recounts his academic life and career. JEL: B31, D00